(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
One of the most important problems in teaching the German language is the problem of the formation and development of lexical skills. It is difficult to overestimate the importance of this problem. Vocabulary is the main resource for ensuring communication and understanding in a foreign language. Without knowledge of vocabulary, it is impossible to construct coherent statements. The article discusses the features of teaching vocabulary in German lessons.